APPLICATION OF PROBLEM-BASED LEARNING TECHNOLOGY IN THE PEDAGOGICAL ACTIVITY OF TEACHERS OF VOCATIONAL COLLEGES (Innovative professional education, 2025)
The possibilities of applying problem-based learning technology in vocational colleges for the development of instructors’ pedagogical activity are analyzed. The creation of learning situations that stimulate active student participation, the development of critical thinking, and the formation of professional competencies are discussed. Special attention is given to adapting the educational process under martial law conditions, particularly in ensuring psychological and pedagogical support for students who have experienced stressful situations. Methodological approaches to integrating case methods, facilitation, and inclusive technologies in professional education are presented
Keywords: problem-based learning, vocational colleges, pedagogical activity, critical thinking, professional competencies, case method, facilitation, inclusive learning, adaptive learning, psychological support